Spanish consensus document for acceptance and rejection of kidneys from expanded criteria donors. (11th September 2014) - Lledó‐García, E.; Riera, L.; Passas, J.; Paredes, D.; Morales, J. M.; Sánchez‐Escuredo, A.; Burgos‐Revilla, F. J.; de Andrés Belmonte, A.; Oppenheimer, F.; Rodríguez‐Ferrero, M. L.; Solé, M.; Matesanz, R.; et al.
Abstract In the recent years, more than 60% of available deceased donors are either older than 50 yr or have significant vascular comorbidities. This makes the acceptance and rejection criteria of renal allografts very rigorous, especially in cases of younger recipients, and at the same time encourages live donations. In our country, there is a lack of homogeneity in the percentages of use of expanded criteria donor (ECD) allografts between the different autonomous communities. Furthermore, the criteria vary greatly, and in some cases, great importance is given to the biopsy while in others very little. In this study, we present a unified and homogenous criteria agreed upon by consensus of a 10‐member Panel representing major scientific societies related to renal transplantation in Spain. The criteria are to be used in accepting and/or rejecting kidneys from the so‐called ECDs. The goal was to standardize the use of these organs, to optimize the results, and most importantly to provide for the maximum well being of our patients. Finally, we believe that after taking into account the Panel's thorough review of specific scientific literature, this document will be adaptable to other national renal transplant programmes.